Pengaruh Leverage, Profitabilitas, dan Ukuran Perusahan terhadap Audit Delay pada Perusahan yang Terdaftar di Bei Periode Tahun 2020-2022 - Flaviana Seltin Varinda Masto; Diana Airawaty (Economic Reviews Journal, 2024)
This study aims to determine the effect of leverage, profitability and company size on Audit Delay. This study is quantitative using a descriptive approach, and uses secondary data from the official BEI website. The population consists of 404 companies, with a purposive sampling sample of 45 companies. The analysis method uses descriptive statistics, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression analysis and hypothesis testing using the t test and f test. the results of the study indicate that leverage and company size do not affect Audit Delay, while profitability has a positive effect on Audit Delay.